2021
DOI: 10.1099/mgen.0.000437
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis complex lineage 5 exhibits high levels of within-lineage genomic diversity and differing gene content compared to the type strain H37Rv

Abstract: Pathogens of the Mycobacterium tuberculosis complex (MTBC) are considered to be monomorphic, with little gene content variation between strains. Nevertheless, several genotypic and phenotypic factors separate strains of the different MTBC lineages (L), especially L5 and L6 (traditionally termed Mycobacterium africanum ) strains, from each… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…L6 is known to be an opportunistic pathogen owing to mutations in genes essential for growth and contributes toward latent TB burden in West Africa ( de Jong et al, 2005 ; de Jong et al, 2010a ; Gehre et al, 2013 ; Ofori-Anyinam et al, 2017 ). Similar studies for L5 genomics are limited that has been highlighted earlier ( Yeboah-Manu et al, 2017 ; Ates et al, 2018 ; Coscolla et al, 2021 ; Sanoussi et al, 2021 ). A slower response to TB treatment for L6 was observed when compared to other sensu stricto lineages ( Diarra et al, 2018 ).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…L6 is known to be an opportunistic pathogen owing to mutations in genes essential for growth and contributes toward latent TB burden in West Africa ( de Jong et al, 2005 ; de Jong et al, 2010a ; Gehre et al, 2013 ; Ofori-Anyinam et al, 2017 ). Similar studies for L5 genomics are limited that has been highlighted earlier ( Yeboah-Manu et al, 2017 ; Ates et al, 2018 ; Coscolla et al, 2021 ; Sanoussi et al, 2021 ). A slower response to TB treatment for L6 was observed when compared to other sensu stricto lineages ( Diarra et al, 2018 ).…”
Section: Introductionmentioning
confidence: 67%
“…Lineage identification is of considerable significance in tuberculosis control, as it helps in quick diagnosis leading to effective treatment and prevention of potential future outbreaks ( Dou et al, 2017 ; Napier et al, 2020 ). Although extensive studies pertaining to the differentiation of L5 and L6 have been carried out in the past, recent reports revealed the existence of underlying sub-lineages ( Ates et al, 2018 ; Coscolla et al, 2021 ; Sanoussi et al, 2021 ). Methods such as phylogeny and PCA have been used to understand the lineage distribution of L5 and L6, with reports of incongruous clustering of L5 ( Coscolla et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-read sequencing on three geographically distant isolates of L5 suggested that using H37Rv as a reference genome is limiting and showed that the pangenome of L5 could be larger than expected previously (Sanoussi et al, 2021). Preliminary results using de novo alignment using Roary indeed suggests that some L5 may harbor specific genes that are not found in H37Rv (results not shown) (Page et al, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Whole-genome analyses also revealed the existence of genetic diversity within M . africanum L5 and L6 strains [ 9 , 38 40 ] and allowed the construction of detailed MTBC phylogeny trees. It is interesting to note that strains of the M .…”
Section: The Identity Of M Africanummentioning
confidence: 99%